FORMATION OF PROFESSIONAL AND PEDAGOGICAL SKILLS OF A FUTURE COACH BY MEANS OF SPORTS TRAINING - Suprun A.A.; Medvedev E.N.; Terekhin R.N.; Zakrevskaya N.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the role of sports training of students of a higher educational institution of physical culture for the formation of professional and pedagogical skills of coaches. Methods and structure of the study. A survey was conducted among students of the specialization "rhythmic gymnastics" of the Department of Theory and Methods of Gymnastics of Lesgaft University, St. Petersburg, in the direction of 49.04.03 Sports and in the direction of 49.03.01 Physical culture. Results and conclusions. From the analysis of the data obtained, it is concluded that there is a positive transfer of the experience of sports training and competitive activity to the professional and pedagogical skills of the future coach. The education system in sports universities should provide training for both high-class athletes and qualified coaches.